1993
DOI: 10.1113/jphysiol.1993.sp019958
|View full text |Cite
|
Sign up to set email alerts
|

Respiration‐synchronous fluctuations in stroke volume, heart rate and arterial pressure in humans.

Abstract: SUMMARY1. Simultaneous recordings of beat-to-beat left cardiac stroke volume (SV, pulsed ultrasound Doppler), mean arterial pressure (MAP) and heart rate (HR) were obtained in ten healthy young adults during spontaneous respiration at supine rest, before and after cholinergic blockade by atropine (0 035 mg kg-').2. Respiration-synchronous fluctuations in SV, HR, cardiac output (CO) and MAP were quantified by spectral analysis of the recordings of each of these variables.3. Before atropine administration, respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
164
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(183 citation statements)
references
References 33 publications
17
164
2
Order By: Relevance
“…In adult rats, atropine increased HR and decreased the spectral HF peak (29,31). Similar results have been obtained in human adults, in which atropine increased HR and decreased HF spectral power (30,32,38). During sympathetic stimulation, variability of the R-R interval series showed virtually no spectral power in the HF band after atropine (30).…”
Section: Autonomic Function In Preterm Infantssupporting
confidence: 80%
“…In adult rats, atropine increased HR and decreased the spectral HF peak (29,31). Similar results have been obtained in human adults, in which atropine increased HR and decreased HF spectral power (30,32,38). During sympathetic stimulation, variability of the R-R interval series showed virtually no spectral power in the HF band after atropine (30).…”
Section: Autonomic Function In Preterm Infantssupporting
confidence: 80%
“…Data shown are from a male (28 years) and the mean heart rate was 53 beats min -1 with HF and LF components of 56.8 NU and 39.1 NU respectively, when supine. During HUT, the mean heart rate was 86 beats min -1 with HF and LF components of 28.6 NU and 63.4 NU respectively J Physiol Sci (2009) 59: 31-36 33 ventilation, as shown by others [23][24][25][26][27]. Also, in the current study, a decrease in HF cardiac variability was shown with HUT, again similar to the findings of others [14,[18][19][20]33].…”
Section: Discussionsupporting
confidence: 91%
“…However, directional changes in the LF component of HRV with tilting appear equivocal, with no change [14,18,21] or an increase [19,20,22] being reported for healthy subjects. Hypercapnia has consistently been shown to increase HF cardiac variability [7,[23][24][25], suggestive of an increase in respiratory sinus arrhythmia [24,[26][27][28] but shown to have variable effects on LF variability [29].…”
Section: Introductionmentioning
confidence: 99%
“…Though not conclusive as they are drawn on a single subject, these results suggest a higher sensitivity of the cTE, compared with the traditional TE, in the detection of information transfers that can be associated to known cardiovascular and cardiorespiratory mechanisms. These mechanisms, also recently investigated using tools based on transfer entropy [7], are the baroreflex modulation of heart rate, manifested through coupling from systolic pressure to heart period variability [39], and the effects of respiration on heart period (describing the so-called respiratory sinus arrhythmia [40]) and on arterial pressure (describing the mechanical perturbations of arterial pressure originating from respiration-related movements [41]). In particular, the higher sensitivity of cTE to the information transferred from systolic pressure to heart period, denoted in this example by the significant values observed for cTE′ Y→Z but not for TE Y→Z in both conditions, could suggest a major role played by fast vagal effects −whereby the systolic pressure affects heart period within the same heartbeat-in the functioning of the baroreflex mechanism.…”
Section: Cardiovascular and Cardiorespiratory Variabilitymentioning
confidence: 99%